Commonly used anti–von Willebrand factor antibody for multimer analysis cross‐reacts with fibronectin, which is difficult to distinguish from von Willebrand factor. Issue 6 (18th September 2021) - Eura, Yuka; Kokame, Koichi
Abstract: Von Willebrand factor (VWF) is a 500‐ to 15 000‐kDa multimeric protein circulating in the blood. When VWF has a higher molecular weight, its hemostatic activity is greater. The size distribution of VWF multimers is usually analyzed by SDS‐agarose gel electrophoresis followed by immunoblotting. We found that the most commonly used anti‐VWF antibody cross‐reacted with fibronectin in VWF multimer analysis. In addition, since the apparent molecular weights of VWF and fibronectin are almost identical, these molecules were difficult to distinguish by SDS‐polyacrylamide gel electrophoresis followed by immunoblotting. Cross‐reactivity between the anti‐VWF antibody and fibronectin was inhibited by pretreating the antibody with fibronectin‐coated plates. To obtain accurate data using anti‐VWF antibodies, it is necessary to be aware of the possibility of cross‐reactivity with fibronectin.